Reasons of the problems that academicians experience in management of teaching and learning process - Süleyman Göksoy (Journal of Pedagogical Research, 2018)
The present research aims to examine the problems that academicians experience in management of teaching-learning process, to reveal the reasons of the problems and to develop solution suggestions. Case study design of qualitative research methods was used in this research and it includes 41 volunteer academicians. Structured interview form was used in data collection and the data were analyzed with content analysis. It was found that most of the problems academicians experience in management of teaching-learning process were related to students. They also had problems with classroom/course management. In management of teaching-learning processes of the academicians, problems were related to students, physical infrastructure, educational system and society/environment. It can be asserted that most of the problems can be solved if their reasons are determined and handled. Also it is suggested that incoming academicians who are new to academic life need to follow the regulations that includes student discipline regulations and the students need to be informed about the negative behaviors and their consequences at the beginning of the term.